The distributional impact of subsidies to higher education: Empirical evidence from Germany - Salvatore Barbaro (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2002)
This paper presents empirical evidence on the distributional impact of public higher edu- cation through analysis of a cross-sectional view of West Germany in 1997. In contrast to a widely-held hypothesis in economics, our findings do not show evidence for a regressive im- pact. The use of a net-transfer calculation clearly provides a progressive distributional effect of the benefits from subsidization - at least when viewed in the cross-sectional perspective. The decisive factors are (1) the general social stratification within and among the adjusted income deciles and (2) the incidence of the granted benefits. Complementary to the existing widespread literature in this field, we propose the BCa-bootstrap procedure in order to perform statistical inference.
Keywords: 330; Hochschulfinanzierung; Studienfinanzierung; Subvention; Steuerinzidenz; Einkommensverteilung; Schätzung; Deutschland